Contributions of Open Biomass Burning and Crop Straw Burning to Air Quality: Current Research Paradigm and Future Outlooks - Mehmood, Khalid; Bao, Yansong; Saifullah,; Bibi, Sadia; Dahlawi, Saad; Yaseen, Muhammad; Abrar, Muhammad Mohsin; Srivastava, Prashant; Fahad, Shah; Faraj, Turki Kh. (Frontiers in Environmental Science, 2022)
Since open biomass burning (OBB) and open crop straw burning (OCSB) could pose a great risk to human health via altering air quality, and these practices have grabbed considerable attention from the scientific community and policymakers. In order to have a greater and deeper understanding of the impact of both OBB and OCSB on air quality, a bibliometric analysis was performed using the Web of Science core collection (WoSCC) to understand the research developments and future perspectives of these issues between 1991 and 2021. VOSviewer software 1.6.15 and R version 4.0.3 were employed to determine the annual scientific production trend, and the role of countries, institutions, authors, and journal metrics network analysis. The findings showed that the interest in the study of OBB and OCSB pollution related to air quality has increased significantly over the last decade. A total of 1021 publications were retrieved with English as the most preferably used language. Among all documents, research articles were the most commonly appeared document type and the researchers mainly emphasized environmental science, meteorology, atmospheric sciences, energy fuels and environmental engineering fields. In terms of article analysis, Atmospheric Chemistry Physics followed by Atmospheric Environment were found the leading journal in this research domain, whereas the most frequently utilized keywords in the documents were biomass, biomass burning, and PM2.5. The most highly impactful article (HIA) published by Bond et al. (2013) in Journal of Geophysical Research-Atmospheres with 2602 total citations and grabbed 289.11 average citations per year between 2011 and 2021. In terms of countries, the USA emerged as the leader with the highest publication rate followed by China and India. The Chinese Academy of Sciences was ranked first in the list of most productive institutions followed by the University of Montana and the US Forest Service. Based on the analysis, the finer spatial and temporal resolution, and characterization and understanding of the complex processes that are occurring in the atmosphere, such as clustering, oxidation, surface chemistry and their impact on air quality, need to be explored in depth. Our research analysis can provide a baseline for future studies in air quality.